First evidence of superiority of Si nanonet field effect transistors over multi-parallel Si nanowire ones in view of electrical DNA hybridization detection. (3rd October 2018) - Nguyen, Thi Thu Thuy; Legallais, Maxime; Morisot, Fanny; Cazimajou, Thibauld; Stambouli, Valérie; Mouis, Mireille; Salem, Bassem; Ternon, Céline
Abstract: Si nanonets (SiNN, networks of randomly oriented Si nanowires) and multi-parallel silicon nanowires (MP-SiNW) were integrated into field effect transistor using standard and low cost microelectronic technologies. The SiNN field effect transistors exhibit high initial ON-state current (in the range of 10 –7 A), ION /IOFF ratio up to 10 4 and rather homogeneous transfer characteristics. In contrast, the MP-SiNW ones present smaller modulation between ON and OFF currents, higher IOFF and more scattered electrical characteristics. In view of DNA hybridization detection, a simple and eco-friendly functionalization process with glycidyloxypropyltrimethoxysilane (GOPS) was used to covalently graft single strand DNA probes on both SiNN and MP-SiNW devices. Validated by fluorescence measurement, DNA hybridization leads to a systematic decrease of ON-state current of SiNN devices. In addition, SiNN-based sensors exhibit more homogeneous and reproducible current variation in response to DNA hybridization step as compared to MP-SiNW configuration. This result highlights the better sensing performances of SiNN FETs as compared to MP-SiNW ones and emphasizes the SiNN potential for label-free detection of DNA.